Anticorrosive paint as well as preparation method and application thereof
By using anticorrosion coatings containing specific composite acids and nanocomposites on the distribution box shell, the problem of corrosion in the distribution box shell is solved, high corrosion resistance and insulation performance are achieved, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202510145376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The housing of the distribution box is susceptible to corrosion, resulting in a shorter service life and an increased maintenance cost, affecting the reliability and safety of power supply.
A anticorrosion coating is developed, which contains a composite acid composed of fumaric acid and para-hydroxybenzenesulfonic acid of a specific weight ratio, and a nanocomposite composed of nanosilicon nitride and nanozinc oxide, to improve the corrosion resistance and insulation of the coating by forming a stable and dense mesh structure.
This anticorrosion coating not only has high corrosion resistance, but also has insulation properties. It can effectively prevent leakage, extend the service life of the distribution box, reduce maintenance costs, and improve the reliability and safety of power supply.
Smart Images

Figure BDA0005266293780000061 
Figure BDA0005266293780000071 
Figure BDA0005266293780000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and more specifically, to an anti-corrosion coating and a preparation method and application thereof. Background Art
[0002] As an important part of the power system, the distribution box is widely used in industrial and civil buildings, and undertakes the functions of power distribution and control. The distribution box shell is a barrier that separates the distribution box from the external environment and protects the internal devices of the distribution box from interference from the external environment. At present, the materials of the distribution box shell are mainly metal, alloy, plastic, composite material, etc. Among them, the distribution box shell made of metal or alloy is widely used because of its high mechanical strength and strong safety, but its susceptibility to corrosion limits the service life of the distribution box shell. In particular, the distribution box is exposed to the outdoor environment all year round, making the metal or alloy distribution box shell susceptible to erosion by rain, ultraviolet rays and other climatic factors, resulting in corrosion, rust, aging and other problems in the distribution box shell. This not only reduces the service life of the distribution box, but also increases the maintenance cost of the distribution box, seriously affecting the reliability and safety of the power supply, so it is very necessary to carry out anti-corrosion on the distribution box shell.
[0003] Coating or spraying anti-corrosion paint on the outer shell of the distribution box is an important anti-corrosion measure for the outer shell of the distribution box. The anti-corrosion paint used must not only have corrosion resistance, but also have insulation properties. This can prevent leakage, extend the service life of the distribution box, reduce the maintenance cost of the distribution box, and ensure the reliability and safety of the power supply.
[0004] Therefore, developing an anti-corrosion coating with high corrosion resistance and insulation is of great economic value. Summary of the invention
[0005] The purpose of the present invention is to solve the deficiencies in the prior art and to provide an anti-corrosion coating and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides an anti-corrosion coating comprising the following components in parts by weight:
[0008] Epoxy resin 50-70 parts, composite acid 25-45 parts, nanocomposite 12-18 parts, isocyanate 4-6 parts, leveling agent 8-12 parts, filler 8-12 parts, antioxidant 4-6 parts, pigment 5-20 parts, diluent 80-120 parts;
[0009] The composite acid contains fumaric acid and p-hydroxybenzenesulfonic acid in a weight ratio of 1:(0.5-2.5);
[0010] The nano composite contains nano boron nitride, nano silicon dioxide and nano zinc oxide.
[0011] In the anti-corrosion coating of the present invention, the composite acid composed of fumaric acid and p-hydroxybenzenesulfonic acid in a specific weight ratio can not only form a stable and dense network structure with epoxy resin, isocyanate, etc. in the system through hydrogen bonds, benzene rings, etc., which can resist the penetration of acidic and alkaline corrosive substances and improve the corrosion resistance of the anti-corrosion coating, but also can increase the volume resistance of the anti-corrosion coating, thereby improving the insulation of the anti-corrosion coating.
[0012] Preferably, the weight ratio of the fumaric acid to p-hydroxybenzenesulfonic acid is 1:(1.0-2.0).
[0013] More preferably, the weight ratio of fumaric acid to p-hydroxybenzenesulfonic acid is 1:1.5.
[0014] Preferably, the weight ratio of the nano-boron nitride, nano-silicon dioxide and nano-zinc oxide is 1:(0.05-0.30):(0.10-0.90).
[0015] More preferably, the weight ratio of the nano-boron nitride, nano-silicon dioxide and nano-zinc oxide is 1:(0.10-0.25):(0.25-0.80).
[0016] In the anti-corrosion coating of the present invention, the nano-composite composed of nano-boron nitride, nano-silicon dioxide and nano-zinc oxide in a specific weight ratio is evenly distributed in the network structure formed by the composite acid, epoxy resin, isocyanate, etc. to further improve the stability, density and strength of the network structure, thereby better resisting the penetration of acidic and alkaline corrosive substances, and better improving the volume resistance of the anti-corrosion coating, thereby further improving the corrosion resistance and insulation of the anti-corrosion coating.
[0017] More preferably, the weight ratio of the nano-boron nitride, nano-silicon dioxide and nano-zinc oxide is 1:0.17:0.5.
[0018] Preferably, the average particle size of the nano boron nitride is 100-500 nm.
[0019] More preferably, the average particle size of the nano-boron nitride is 200-400 nm.
[0020] Preferably, the average particle size of the nano-silicon dioxide is 50-200 nm.
[0021] More preferably, the average particle size of the nano-silicon dioxide is 80-120 nm.
[0022] Preferably, the average particle size of the nano zinc oxide is 40-150 nm.
[0023] More preferably, the average particle size of the nano zinc oxide is 40-60 nm.
[0024] Epoxy resins, isocyanates, leveling agents, fillers, antioxidants, pigments, and diluents commonly used in the art can all be used in the present invention.
[0025] Preferably, the isocyanate is at least one of hexamethylene diisocyanate and isophorone diisocyanate.
[0026] Preferably, the leveling agent is BYK-333.
[0027] Preferably, the filler is at least one of aluminum hydroxide, double fly ash, mica powder, talcum powder and bentonite.
[0028] More preferably, the filler is aluminum hydroxide and double fly ash in a weight ratio of 1:(3-6).
[0029] Preferably, the antioxidant is at least one of antioxidant 9614 and antioxidant 1010.
[0030] Preferably, the pigment is at least one of titanium dioxide, chrome yellow, molybdate chrome red and chrome green.
[0031] Preferably, the diluent is at least one of acetone, ethanol, ethyl acetate and toluene.
[0032] In a second aspect, the present invention provides a method for preparing an anti-corrosion coating, comprising the following steps:
[0033] S1. Divide the diluent into three parts, namely diluent I, diluent II, and diluent III, for later use;
[0034] S2. Add fumaric acid, epoxy resin and nanocomposite to diluent Ⅰ to obtain component Ⅰ for standby use;
[0035] S3. Add p-hydroxybenzenesulfonic acid and isocyanate to diluent II to obtain component II for standby use;
[0036] S4. Add a leveling agent, a filler, an antioxidant, and a pigment to the diluent III to obtain component III for standby use;
[0037] S5. Heat component I, add component II and mix, cool down, and then add component III to obtain the anti-corrosion coating.
[0038] In the present invention, the weight proportions of diluent I, diluent II and diluent III may be the same or different.
[0039] Preferably, the step S2 specifically comprises: adding fumaric acid to the diluent I, performing a first heating and then adding epoxy resin, performing a second heating and then adding the nanocomposite to obtain component I for standby use.
[0040] More preferably, the temperature of the first heating is 30-40°C.
[0041] More preferably, the temperature of the second heating is 90-100°C.
[0042] Preferably, in step S5, the heating temperature is 70-80°C.
[0043] Preferably, in step S5, the cooling temperature is 40-50°C.
[0044] In a third aspect, the present invention provides an application of an anti-corrosion coating in a distribution box.
[0045] Preferably, the anti-corrosion coating is provided on the outer shell surface of the distribution box.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] In the anti-corrosion coating of the present invention, the composite acid composed of fumaric acid and p-hydroxybenzenesulfonic acid in a specific weight ratio can not only form a stable and dense network structure with epoxy resin, isocyanate, etc. in the system through hydrogen bonds, benzene rings, etc., which can resist the penetration of acidic and alkaline corrosive substances and improve the corrosion resistance of the anti-corrosion coating, but also can increase the volume resistance of the anti-corrosion coating, thereby improving the insulation of the anti-corrosion coating.
[0048] In the anti-corrosion coating of the present invention, the nano-composite composed of nano-boron nitride, nano-silicon dioxide and nano-zinc oxide in a specific weight ratio is evenly distributed in the network structure formed by the composite acid, epoxy resin, isocyanate, etc. to further improve the stability, density and strength of the network structure, thereby better resisting the penetration of acidic and alkaline corrosive substances, and better improving the volume resistance of the anti-corrosion coating, thereby further improving the corrosion resistance and insulation of the anti-corrosion coating.
[0049] The anti-corrosion coating of the present invention not only has corrosion resistance but also has insulation performance, so it can prevent leakage, extend the service life of the distribution box, reduce the maintenance cost of the distribution box, and ensure the reliability and safety of power supply. DETAILED DESCRIPTION
[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0051] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or according to conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0052] In each embodiment and comparative example of the present invention, the use of reagents is as follows:
[0053] Epoxy resin, WSR618 (E51), Phoenix brand;
[0054] Nano boron nitride-1, average particle size 300nm, Brofos-BN-300, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0055] Nano boron nitride-2, average particle size 400nm, Brofos-BN-400, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0056] Nano boron nitride-3, average particle size 200nm, Brofos-BN-200, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0057] Nano boron nitride-4, average particle size 100 nm, Brofos-BN-100, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0058] Nano boron nitride-5, average particle size 500nm, Brofos-BN-500, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0059] Nano-silicon dioxide-1, average particle size 100 nm, Brofos-SiO2-100, Brofos Nano-Tech (Ningbo) Co., Ltd.;
[0060] Nano zinc oxide-1, average particle size 50 nm, Brofos-ZnO-50, Brofos Nanotechnology (Ningbo) Co., Ltd.;
[0061] Nano zinc oxide-2, average particle size 150 nm, Brofos-ZnO-150, Brofos Nanotechnology (Ningbo) Co., Ltd.
[0062] Leveling agent, BYK-333, BYK, Germany;
[0063] Antioxidant, antioxidant 9614, CAS number: 2408518-51-2, Qingdao Jiedejia New Material Technology Co., Ltd.;
[0064] Double fly powder, mesh size is 400 mesh, Jiangxi Xuerui Powder New Material Co., Ltd.;
[0065] Aluminum hydroxide, particle size 25 μm, A110531, Shanghai Aladdin;
[0066] Titanium dioxide, R-248, Sichuan Pangang Titanium Industry.
[0067] Example 1
[0068] This embodiment provides an anti-corrosion coating, comprising the following components in parts by weight:
[0069] 60 parts of epoxy resin, 33 parts of composite acid, 15 parts of nanocomposite, 5 parts of isocyanate (hexamethylene diisocyanate), 10 parts of leveling agent, 10 parts of filler, 5 parts of antioxidant, 7 parts of pigment titanium dioxide, and 100 parts of diluent acetone;
[0070] The composite acid contains fumaric acid and p-hydroxybenzenesulfonic acid in a weight ratio of 1:1.5;
[0071] The nanocomposite contains nano boron nitride-1, nano silicon dioxide-1 and nano zinc oxide-1 in a weight ratio of 1:0.17:0.5;
[0072] The filler is aluminum hydroxide and double fly ash in a weight ratio of 1:4;
[0073] The preparation method of the above-mentioned anticorrosive coating comprises the following steps:
[0074] S1. Divide the diluent acetone into three equal parts, namely diluent I, diluent II, and diluent III, for later use;
[0075] S2. Add fumaric acid to the diluent Ⅰ, heat to 35 ℃ for the first time and then add epoxy resin, heat to 95 ℃ for the second time and then add the nanocomposite to obtain component Ⅰ, set aside;
[0076] S3. Add p-hydroxybenzenesulfonic acid and isocyanate (hexamethylene diisocyanate) to diluent II to obtain component II for standby use;
[0077] S4. Add a leveling agent, a filler, an antioxidant, and a pigment titanium dioxide to the diluent III to obtain component III for standby use;
[0078] S5. Heat component I to 75°C, add component II and mix, cool down to 45°C, and then add component III to obtain the anti-corrosion coating.
[0079] Examples 2-5 and Comparative Examples 1-3
[0080] Examples 2-5 and Comparative Examples 1-3 provide different anticorrosive coatings, which differ from Example 1 in that the weight ratio of fumaric acid to p-hydroxybenzenesulfonic acid in the composite acid is different, and the rest is consistent with Example 1, as shown in the following table:
[0081] Table 1 Weight ratio of fumaric acid and p-hydroxybenzenesulfonic acid in Examples 1-5 and Comparative Examples 1-3
[0082] Weight ratio of fumaric acid to p-hydroxybenzenesulfonic acid Example 1 1:1.5 Example 2 1:2.0 Example 3 1:1.0 Example 4 1:2.5 Example 5 1:0.5 Comparative Example 1 1:5 Comparative Example 2 1:0 Comparative Example 3 0:1
[0083] Comparative Example 4
[0084] This comparative example provides an anti-corrosion coating, which differs from Example 1 in that maleic acid replaces p-hydroxybenzenesulfonic acid, and the rest is consistent with Example 1.
[0085] Examples 6-13 and Comparative Examples 5-7
[0086] Examples 6-13 and Comparative Examples 5-7 provide different anticorrosive coatings, which differ from Example 1 in that the weight ratios of nano boron nitride-1, nano silicon dioxide-1 and nano zinc oxide-1 in the nanocomposite are different, and the rest are consistent with Example 1, as shown in the following table:
[0087] Table 2 Weight ratio of nano boron nitride-1, nano silicon dioxide-1 and nano zinc oxide-1 in Examples 1, 6-13 and Comparative Examples 5-7
[0088]
[0089]
[0090] Examples 14-17
[0091] Examples 14-17 provide different anti-corrosion coatings, which differ from Example 1 in that the types of nano boron nitride are different, and the rest are consistent with Example 1, as shown in the following table:
[0092] Table 3 Types of nano boron nitride in Examples 1, 14-17
[0093] Types of Nano Boron Nitride Average particle size of nano boron nitride / nm Example 1 Nano Boron Nitride-1 300 Embodiment 14 Nano Boron Nitride-2 400 Embodiment 15 Nano Boron Nitride-3 200 Example 16 Nano Boron Nitride-4 100 Embodiment 17 Nano Boron Nitride-5 500
[0094] Embodiment 18
[0095] This embodiment provides an anti-corrosion coating, which differs from Embodiment 1 in that nano zinc oxide-2 (average particle size 150 nm) is used instead of nano zinc oxide-1 (average particle size 50 nm), and the rest is consistent with Embodiment 1.
[0096] Embodiment 19
[0097] This embodiment provides an anti-corrosion coating, comprising the following components in parts by weight:
[0098] 50 parts of epoxy resin, 25 parts of composite acid, 12 parts of nanocomposite, 4 parts of isocyanate (hexamethylene diisocyanate), 8 parts of leveling agent, 8 parts of filler, 4 parts of antioxidant, 5 parts of pigment titanium dioxide, 80 parts of diluent acetone;
[0099] The composite acid contains fumaric acid and p-hydroxybenzenesulfonic acid in a weight ratio of 1:0.7;
[0100] The nanocomposite contains nano boron nitride-1, nano silicon dioxide-1 and nano zinc oxide-1 in a weight ratio of 1:0.10:0.25;
[0101] The filler is aluminum hydroxide and double fly ash in a weight ratio of 1:3;
[0102] The preparation method of the above anti-corrosion coating is consistent with that of Example 1.
[0103] Embodiment 20
[0104] This embodiment provides an anti-corrosion coating, comprising the following components in parts by weight:
[0105] 70 parts of epoxy resin, 45 parts of composite acid, 18 parts of nanocomposite, 6 parts of isocyanate (hexamethylene diisocyanate), 14 parts of leveling agent, 12 parts of filler, 6 parts of antioxidant, 20 parts of pigment titanium dioxide, and 120 parts of diluent acetone;
[0106] The composite acid contains fumaric acid and p-hydroxybenzenesulfonic acid in a weight ratio of 1:2.5;
[0107] The nanocomposite contains nano boron nitride-1, nano silicon dioxide-1 and nano zinc oxide-1 in a weight ratio of 1:0.25:0.80;
[0108] The filler is aluminum hydroxide and double fly ash in a weight ratio of 1:6;
[0109] The preparation method of the above anti-corrosion coating is consistent with that of Example 1.
[0110] Performance Testing
[0111] The performance tests of the anticorrosive coatings of the embodiments and comparative examples are as follows:
[0112] (1) Sample preparation
[0113] The anticorrosive coating of each embodiment or comparative example was coated on a stainless steel plate and baked at 200° C. for 10 min to obtain a coating sample with a length of 10 mm, a width of 30 mm, and a thickness of 100 μm;
[0114] (2) Tensile strength test
[0115] The coating sample prepared in (1) was subjected to stress-strain test using a CMT5305 universal testing machine, with a strain rate of 10 mm / min. The tensile strength refers to the load per unit cross-sectional area when the coating sample is broken on the CMT5305 universal testing machine.
[0116] (3) Corrosion resistance test
[0117] In the present invention, the corrosion resistance of the anticorrosive coating is reflected by the strength of the acid corrosion resistance and the alkali corrosion resistance;
[0118] A. Acid resistance test
[0119] The coating sample prepared in (1) was immersed in 20L of 10% hydrochloric acid aqueous solution for 45 days, taken out, and the surface conditions of the coating sample were observed and recorded for rating, wherein "0" means that the coating sample surface has no wrinkles, no bubbles, and no peeling, "1" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤15% and >0%, "2" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤50% and >15%, and "3" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤100% and >50%;
[0120] B. Alkali resistance test
[0121] The coating sample prepared in (1) was immersed in 20L of 10% sodium hydroxide aqueous solution for 45 days, taken out, and the surface conditions of the coating sample were observed and recorded for rating, wherein "0" means that the coating sample surface has no wrinkles, no bubbles, and no peeling, "1" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤15% and >0%, "2" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤50% and >15%, and "3" means that the area of wrinkles, bubbles, and peeling on the coating sample surface is ≤100% and >50%;
[0122] (4) Insulation test
[0123] Referring to the QJ2220.2-92 standard, at a voltage of 250 V, with 0.01 mm annealed aluminum foil as the electrode material, the volume resistivity of the coating sample prepared by (1) was measured; the larger the volume resistivity, the stronger the insulation of the anti-corrosion coating;
[0124] The experimental results are shown in the following table:
[0125] Table 4 Performance test results of the anticorrosive coatings of various embodiments and comparative examples
[0126]
[0127]
[0128] It can be seen from Table 4 that the anti-corrosion coating of the present invention not only has corrosion resistance but also has insulation performance.
[0129] By comparing Examples 1-5 and Comparative Examples 1-4, it can be seen that in the anti-corrosion coating of the present invention, the composite acid composed of fumaric acid and p-hydroxybenzenesulfonic acid in a specific weight ratio can not only form a stable and dense network structure with epoxy resin, isocyanate, etc. in the system through hydrogen bonds, benzene rings, etc., which can resist the penetration of acidic and alkaline corrosive substances and improve the corrosion resistance of the anti-corrosion coating, but also can increase the volume resistance of the anti-corrosion coating, thereby improving the insulation of the anti-corrosion coating.
[0130] By comparing Examples 1, 6-13 and Comparative Examples 5-7, it can be seen that in the anti-corrosion coating of the present invention, the nano-composite composed of nano-boron nitride, nano-silicon dioxide and nano-zinc oxide in a specific weight ratio is evenly distributed in the network structure formed by composite acid, epoxy resin, isocyanate, etc., to further improve the stability, density and strength of the network structure, thereby better resisting the penetration of acidic and alkaline corrosive substances, and better improving the volume resistance of the anti-corrosion coating, thereby further improving the corrosion resistance and insulation of the anti-corrosion coating.
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An anti-corrosion coating, characterized in that: The composition comprises the following components in parts by weight: Epoxy resin 50-70 parts, composite acid 25-45 parts, nanocomposite 12-18 parts, isocyanate 4-6 parts, leveling agent 8-12 parts, filler 8-12 parts, antioxidant 4-6 parts, pigment 5-20 parts, diluent 80-120 parts; The composite acid contains fumaric acid and p-hydroxybenzenesulfonic acid in a weight ratio of 1:(0.5-2.5); The nano composite contains nano boron nitride, nano silicon dioxide and nano zinc oxide.
2. The anticorrosive coating according to claim 1, characterized in that: The weight ratio of the fumaric acid to p-hydroxybenzenesulfonic acid is 1:(1.0-2.0).
3. The anticorrosive coating according to claim 1, characterized in that: The weight ratio of the nano boron nitride, nano silicon dioxide and nano zinc oxide is 1:(0.05-0.30):(0.10-0.90).
4. The anticorrosive coating according to claim 3, characterized in that: The weight ratio of the nano boron nitride, nano silicon dioxide and nano zinc oxide is 1:(0.10-0.25):(0.25-0.80).
5. The anticorrosive coating according to claim 1, characterized in that: Including at least one of the following (1)-(3): (1) The average particle size of the nano boron nitride is 100-500nm; (2) The average particle size of the nano-silicon dioxide is 50-200 nm; (3) The average particle size of the nano zinc oxide is 40-150 nm.
6. The anticorrosive coating according to claim 5, characterized in that: Including at least one of the following (1)-(3): (1) The average particle size of the nano boron nitride is 200-400 nm; (2) The average particle size of the nano-silicon dioxide is 80-120 nm; (3) The average particle size of the nano zinc oxide is 40-60 nm.
7. The anticorrosive coating according to claim 1, characterized in that: Including at least one of the following (1)-(6): (1) The isocyanate is at least one of hexamethylene diisocyanate and isophorone diisocyanate; (2) The leveling agent is BYK-333; (3) The filler is at least one of aluminum hydroxide, double fly ash, mica powder, talc, and bentonite; (4) The antioxidant is at least one of antioxidant 9614 and antioxidant 1010; (5) The pigment is at least one of titanium dioxide, chrome yellow, molybdenum chrome red and chrome green; (6) The diluent is at least one of acetone, ethanol, ethyl acetate and toluene.
8. The anticorrosive coating according to claim 7, characterized in that: The filler is aluminum hydroxide and double fly ash in a weight ratio of 1:(3-6).
9. A method for preparing the anticorrosive coating according to any one of claims 1 to 8, characterized in that: The steps include: S1. Divide the diluent into three parts, namely diluent I, diluent II, and diluent III, for later use; S2. Add fumaric acid, epoxy resin and nanocomposite to diluent Ⅰ to obtain component Ⅰ for standby use; S3. Add p-hydroxybenzenesulfonic acid and isocyanate to diluent II to obtain component II for standby use; S4. Add a leveling agent, a filler, an antioxidant, and a pigment to the diluent III to obtain component III for standby use; S5. Heat component I, add component II and mix, cool down, and then add component III to obtain the anti-corrosion coating.
10. Use of the anti-corrosion coating according to any one of claims 1 to 8 in a distribution box.
Citation Information
Patent Citations
Insulation column for power equipment
CN108492943A
Hyperbranched epoxy oligosiloxane high-wear-resistance heavy-duty anticorrosive paint as well as preparation method and application thereof
CN113845842A
Wear-resistant anticorrosive paint and preparation method thereof
CN118480299A
Composition Including Ceramic and Polymer Resin for Waterproof, Anticorrosion, Surface-Protection of Concrete and Repair and Reinforcement of Civil Engineering Fabric Eroded Chemically in Treatment Facilities of Sewage and Wastewater and Method for Surface-Protection Using the Same
KR100986711B1
Film-forming binders containing nanoscale particles and featuring enhanced scratch resistance and flexibility, processes for their preparation, and high-transparency coating materials containing them
WO2008049679A1